LGBT DAN HUKUM POSITIF INDONESIA - Fatimah Asyari (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
In Indonesia alone LGBT is a taboo and classified as still things that have not fully understood by the people of Indonesia. The Indonesian Laws Act only specifies two genders: men and women. This can be interpreted from the strict inclusion of men and women in the Marriage Act (UU No. 1/1974) and similar provisions concerning the contents of citizen cards stipulated in the Population Administration Act (UU No. 23/2006). In Indonesia's positive law especially the Criminal Code (Criminal Code) LGBT legality itself does not exist. However, in terms of homosexual status there are arrangements in Indonesia, there are criminal rules related to same-sex relationships contained in Article 292 of the Criminal Code. This type of punishment, in the Criminal Code Article 292 with the threat of imprisonment of 5 years in prison. There is no legal rule in the Criminal Code that regulates LGBT more explicitly. The need for a thorough change in the Criminal Code Article 292 and a clearer explanation for sanctions for homosexuals in criminal law. Law enforcement officers must take concrete action in tackling the homosexual case in the community.